In pursuit of early mammals - Kielan-Jaworowska, Zofia (Life of the past., 2013)
This book presents the history of the mammals that lived during the Mesozoic era - the time when dinosaurs ruled the Earth - and describes their origins, anatomy, systematics, paleobiology, and distribution. It also tells the story of the author, a world-renowned specialist on these animals, and the other prominent paleontologists who have studied them. The author was the first woman to lead large-scale paleontological expeditions, including eight to the Gobi Desert in Mongolia, which brought back important collections of dinosaur, early mammal, and other fossils. In this book, she shares the difficulties and pleasures encountered in finding rare fossils and describes the changing views on early mammals made possible by these discoveries.